PENGARUH KOMPENSASI, KEMAMPUAN, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. COCA COLA AMATIL INDONESIA BALI DI DENPASAR - Surya Firmansyah; I Wayan Mendra; Yenny Verawati (EMAS, 2021)
Coca Cola Amatil Indonesia Bali as one of the big companies in Indonesia certainly needs good employee performance in order to achieve the stated company goals. But currently PT. Coca Cola Amatil Indonesia Bali is experiencing problems regarding the performance of these employees which can be seen from the high level of absenteeism which may be caused by employee dissatisfaction with the compensation provided by the company and training that has not been able to improve the ability of employees to complete their work and provide better results than before. This study aims to test and obtain empirical evidence of the effect of compensation, work ability, and job satisfaction on employee performance at PT. Coca Cola Amatil Indonesia Bali in Denpasar. The population in this study were all employees of PT. Coca Cola Amatil Indonesia Bali in Denpasar as many as 125 people. The sample was determined using the Slovin formula in order to obtain 56 people as a sample, and samples were taken using random sampling techniques. The analytical tool used is multiple linear regression analysis, analysis of determination, and t test. The results of this study indicate that compensation has a positive and significant effect on employee performance at PT. Coca Cola Amatil Indonesia Bali, work ability has a positive and significant effect on employee performance at PT. Coca Cola Amatil Indonesia Bali, and job satisfaction have a positive and significant effect on employee performance at PT. Coca Cola Amatil Indonesia Bali. It is recommended to PT. Coca Cola Amatil Indonesia Bali to provide salaries by looking at the tasks and workloads carried out by employees, providing trainings on existing jobs, and it is recommended to give awards to employees as a form of company appreciation for employees so that employees enjoy working at PT. Coca Cola Amatil Indonesia Bali.